Food Taboos and Biblical Prohibitions Reassessing Archaeological and Literary Perspectives - Angelini, Anna; Altmann, Peter; Spiciarich, Abra (Mohr Siebeck, 2020)
This volume presents contributions from »The Larger Context of the Biblical Food Prohibitions: Comparative and Interdisciplinary Approaches« conference held in Lausanne in June, 2017. The biblical food prohibitions constitute an excellent object for comparative and interdisciplinary approaches given their materiality, their nature as comparative objects between cultures, and their nature as an anthropological object. This volume articulates these three aspects within an integrated and dynamic perspective, bringing together contributions from Levantine archaeology, ancient Near Eastern studies, and anthropological and textual perspectives to form a new, multi-disciplinary foundation for interpretation.